Electrospraying Technology and Its Research Progress in Food Field - Wei GAO; Yunshan WEI; Guangsu ZHU; Kunlun LIU; Huiyan ZHANG (Shipin gongye ke-ji)
The non-thermophysical nature of electrospraying has been extensively documented, with high-voltage electrostatic fields being employed to achieve continuous fabrication of micro/nano particulates. Significant attention has been garnered within the food sector, particularly due to the operational advantages including facile processing protocols, ambient condition compatibility, and exceptional encapsulation performance. Therefore, this review systematically reviews the underlying mechanisms of electrospraying, with particular emphasis on the interdependent effects of polymer solution properties, process parameters, and environmental parameters on particulate morphology and encapsulation efficiency. This review systematically categorizes commonly utilized encapsulation materials, encompassing proteins (e.g., zein, whey protein, gelatin) and polysaccharides (e.g., alginate, chitosan, pullulan), with their respective functional properties and application scenarios being comparatively analyzed. Additionally, this review systematically outlines the current applications of electrospraying technology in both bioactive compound encapsulation and advanced food packaging systems. Furthermore, critical analysis is provided on existing technical limitations and future research directions, which aims to establish a theoretical foundation and inspire innovative developments in food-oriented electrospraying research.